Educação infantil em telas: articulações possíveis entre comunicação, educação e tecnologias na produção de videoaulas durante a pandemia de COVID-19 - Morais, Leila Ferreira Gonçalves (2021)
The present research aimed to investigate the video classes produced by the Department of Education of the city of Uberlândia along with the Municipal Center of Studies and Educational Projects Julieta Diniz (CEMEPE) and in a partnership with the Universitary Television of Uberlândia (Fundação RTU). The video classes became necessary options and, therefore, were developed, in the year 2020, during the pandemic of the new Coronavirus, to reach all students from the municipal system, including those from Early Childhood Education, Preschool 4 (four) and 5 (five) years old, first step of Basic Education. In the face of this approach, this study had as general aim to critically analyze the video classes produced for the Preschool, Early Childhood Education, in the municipal public system of the city of Uberlândia MG. On that end, eight video classes produced for Early Childhood Education, posted on the official page of the city hall and on Youtube, were investigated. As a methodology, the qualitative analysis with bibliographic and documental bias was selected - federal legislation and official documents of early childhood education, with descriptive basis and exploratory type. This perspective ran through theoretical discussions from authors such as Ariès (1981), Del Priori (2004), Monarcha (2001) and Kuhlmann Jr. (2015), which deal with the conception of children and childhood, along with an important understanding of early childhood education in Brazil. Concerning communication, education and technology, the ones that stood out were Coscarelli and Ribeiro (2017); Moran, Masetto and Behrens (2013); Costa and Oliveira (2004). In addition to those, the studies of the authors Morettin (1995); Duarte and Alegria (2008); Ferreira (2010); Santos (2018); Comolli (2008) and Hagemeyer (2012) were referred, in order to discuss how the audiovisuals can be significant for school education in the current context. Lastly, the methodological path of the analysis allowed a deep investigation of the elements that composes the audiovisual products selected for this research. Therefore, it is concluded that the intention to use the video was important when attending the emergency situation caused by the social distance. Nevertheless, we must always be alert and reflect on the necessities of the education that is necessary for the children in this pandemic season.